Cross-Presentation of Cell-Associated Antigens by MHC Class I in Dendritic Cell Subsets - Gutiérrez-Martínez, Enric; Planès, Remi; Anselmi, Giorgio; Reynolds, Matthew; Menezes, Shinelle; Adiko, Aimé Cézaire; Saveanu, Loredana; Guermonprez, Pierre (Frontiers in Immunology, 2015)
Dendritic cells have the unique ability to pick up dead cells carrying antigens in tissue and migrate to the lymph nodes where they can cross-present cell-associated antigens by MHC class I to CD8+ T cells. There is strong in vivo evidence that the mouse XCR1+ dendritic cells subset acts as a key player in this process. The intracellular processes underlying cross-presentation remain controversial and several pathways have been proposed. Indeed, a wide number of studies have addressed the cellular process of cross-presentation in vitro using a variety of sources of antigen and antigen presenting cells. Here we review the in vivo and in vitro evidence supporting the current mechanistic models and disscuss their physiological relevance to the cross-presentation of cell-associated antigens by dendritic cells subsets